Time to conception and the menstrual cycle: an observational study of fertility app users who conceived. (8th August 2021) - Bradley, Danielle; Landau, Erin; Jesani, Noreen; Mowry, Brett; Chui, Kenneth; Baron, Alex; Wolfberg, Adam
Abstract: The objective of this research was to evaluate the association between menstrual cycle characteristics (cycle length, cycle-length variability, and their interaction) and the amount of time it takes women to conceive using a robust multiple linear regression. Participants downloaded Ovia Fertility in 2015 indicated that they had just started trying to conceive, and reported conception within 12 months ( n  = 45, 360, adjusted model n  = 8835). The average time to conception among women in the adjusted model was 3.94 months ( n  = 8835). Women with normal cycle lengths (27–29 days) conceived more quickly than women with cycle lengths of 25–26 days (+0.41 months; p  < 0.001), 30–31 days (+0.27 months; p  < 0.01), 32–33 days (+0.44 months; p  < 0.001), and 34+ days (+0.75 months; p  < 0.001). Women with regular cycle-length variability (<9 days between cycles) conceived more quickly than women with irregular variability (+0.72 months; p  < 0.001). Results of the interaction analysis indicated that, among women with regular cycle-length variability, those with normal cycle length had shorter time to conception than women with either short or long cycle length. The interaction between cycle length and cycle-length variability provided enhanced insights into the amount of time it takes to conceive, compared to either indicator alone.